Development of Junior High School Biology Science Learning Tools Using STAD Strategy Through Lesson Study: Its Influence on Students' Critical Thinking Skills - Herinda Mardin; Hartono D. Mamu (Postgraduate, University of Mataram, 2025)
The purpose of this study was to produce a biology science learning device for junior high school with STAD strategy through lesson study that has a significant effect on students' critical thinking skills. This study was conducted in two stages, namely the development research stage which aims to develop biology learning devices and implementation of learning with experiments. The research method is R & D by adapting the 4-D development model from Thiagarajan (1974). Data collection was carried out using tests, observation sheets, and student response questionnaires. Data were analyzed descriptively and inferentially with mancova, and previously data normality and homogeneity tests were carried out. The development of a biology science learning device for junior high school with STAD strategy through lesson study provided several results, namely the learning process was carried out according to the plan that had been made; the student learning process showed an increase towards the better, as an impact of providing motivation, guidance and continuous attention from the model teacher; interaction between students, and interaction between students and teachers increased more than the previous cycle. This is the impact of providing motivation and enthusiasm, as well as reinforcement from the model teacher during learning; Students who still do not participate in group discussions or class discussions need a process and sufficient time to be able to change. Its influence on students' critical thinking skills, the results of critical thinking skills measurements conducted before and after learning, showed a tendency for an increase in the average value of critical thinking skills from pretest to posttest. Based on the learning strategy, the highest average pretest value of critical thinking skills was obtained in the STAD strategy, namely 41.02. The highest average value of critical thinking skills both pretest and posttest was in the upper academic ability, namely 42.41 and 71.94. The results of the study showed that the STAD learning strategy had an effect on critical thinking skills in junior high school biology science learning.